Fate, behavior and ecotoxicology of silver nanoparticles: interactions with natural organic matter in aquatic systems - Watanabe, Cláudia Hitomi [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
When introduced in environment, manufactured nanoparticles (NPs) can interact with biotic and abiotic molecules yielding a transformed NP usually coated with these molecules (natural coating). These different forms of the NPs should be considered as new materials because them distinct properties from the released NPs forms. In fact, these in situ transformations of the NPs have relevant impacts on their toxicological effects, having new or additional risks still not studied. This project aims to determine, understand and predict the impact of natural molecules in the transformations and bio-effects of Ag NPs, widely used as antibacterial agents. Despite the growing interest and use of these NPs, the gathered knowledge on their environmental consequences is still scarce, since the large majority of the studies do not consider the effect of the presence of natural coatings around the particles. In fact, most of the studies do not even determine the effects of the presence of manufactured coatings. Generally, NPs manufacturers add ionic or polymeric coatings to improve their mobility and stabilization in terms of size. Although the possible effects of these manufactured coatings in the NPs behavior there is not systematically studied about their impact. This project aims to overcome the current uncertainty about the environmental safety of manufactured coated NPs, and explore the impact of natural molecules on their environmental risk. The project objectives are: i) characterize the manufactured coated Ag NPs in absence and presence of natural molecules including Humic Substances (HS) and Extracellular Polymeric Substances (EPS), ii) determinate the biocompatible and bioadverse effects of the transformed NPs on the algae Raphidocelis subcapitata and the microcrustacean Daphnia similis and iii) evaluate the transfer of the transformed NPs in the food chain alga-microcrustacean. Thus, this project purposes to introduce a standardized and improved evaluation of the ecotoxicology in order to increase the competitiveness and safety of nanostructured products.

Quando introduzidas no ambiente, nanopartículas (NP) podem interagir com moléculas bióticas e abióticas produzindo uma NP transformada geralmente revestida com essas moléculas (revestimento natural). Essas diferentes formas de NPs devem ser consideradas como novos materiais, pois possuem propriedades distintas dos formulários liberados dos NPs. De fato, essas transformações in situ das NPs apresentam impactos relevantes em seus efeitos toxicológicos, tendo riscos novos ou adicionais ainda não estudados. Este projeto tem como objetivo determinar, entender e prever o impacto de moléculas naturais nas transformações e efeitos biológicos dos NPs de Ag, amplamente utilizados como agentes antibacterianos. Apesar do crescente interesse e uso desses NPs, o conhecimento acumulado sobre suas conseqüências ambientais ainda é escasso, uma vez que a grande maioria dos estudos não considera o efeito da presença de revestimentos naturais ao redor das partículas. De fato, a maioria dos estudos nem sequer determina os efeitos da presença de revestimentos fabricados. Geralmente, os fabricantes de NPs adicionam revestimentos iônicos ou poliméricos para melhorar sua mobilidade e estabilização em termos de tamanho. Embora os possíveis efeitos desses revestimentos fabricados no comportamento dos NPs não sejam sistematicamente estudados sobre seu impacto. Este projeto visa superar a atual incerteza sobre a segurança ambiental de NPs revestidos fabricados e explorar o impacto de moléculas naturais em seus riscos ambientais. Os objetivos do projeto são: i) caracterizar os NPs de Ag revestidos fabricados na ausência e presença de moléculas naturais, incluindo Substâncias Húmicas (HS) e Substâncias Poliméricas Extracelulares (EPS), ii) determinar os efeitos biocompatíveis e bioadversos dos NPs transformados nas algas Raphidocelis subcapitata e o microcrustáceo Daphnia similis e iii) avaliar a transferência dos NPs transformados na cadeia alimentar de microcrustáceos algas. Assim, este projeto tem como objetivo introduzir uma avaliação padronizada e aprimorada da ecotoxicologia, a fim de aumentar a competitividade e a segurança dos produtos nanoestruturados.

Lorsqu'elles sont introduites dans l'environnement, les nanoparticules manufacturées (NPs) peuvent interagir avec des molécules biotiques et abiotiques, produisant des NPs transformées, recouvertes par ces molécules, colloïdes naturels. Ces différentes formes de NP doivent être considérées comme de nouveaux matériaux, car elles ont des propriétés différentes des NPs sources libérées dans le milieu naturel. En fait, ces transformations in situ des NPs ont des impacts significatifs sur leurs effets toxicologiques, avec des risques nouveaux ou supplémentaires peu étudiés. Ce projet vise à déterminer, comprendre et prévoir l’impact des molécules naturelles sur les transformations et les effets biologiques des NPs d’Argent, largement utilisés en tant qu’agents antibactériens. Malgré l'intérêt croissant et l'utilisation de ces NPs, les connaissances recueillies sur leurs conséquences pour l'environnement sont encore rares, car la grande majorité des études ne prend pas en compte l'effet de la présence d’enrobages d’origine naturel autour de ces particules. En fait, la plupart des études ne déterminent même pas les effets de la présence de enrobages manufacturés (par opposition aux enrobages naturels) accompagnant les NPs. Généralement, les fabricants de NP ajoutent des enrobages ioniques ou polymériques pour améliorer la mobilité et la stabilité des NPs et leur impact n’est pas systématiquement étudié. Ce projet vise à surmonter les incertitudes actuelles quant à la sécurité environnementale des nanoparticules enrobées et à explorer l'impact des molécules naturelles sur leur risque environnemental. Les objectifs du projet sont les suivants: i) caractériser les NP Ag avec de enrobages manufacturés en l'absence et en présence de molécules naturelles, y compris les substances humiques (HS) et les substances polymériques extracellulaires (EPS), ii) déterminer les effets positifs et/ou néfastes des NPs ainsi transformées sur l'algue Raphidocelis subcapitata et le micro-crustacé Daphnia similis et iii) évaluer le transfert des NPs transformés dans une chaîne alimentaire modèle simplifiée: algue-micro-crustacé. Ce projet vise donc à introduire une évaluation standardisée et améliorée de l'écotoxicologie afin d'accroître la compétitivité et la sécurité des produits nanostructurés.
Destino, comportamento e ecotoxicologia de nanopartículas de prata: interações com matéria orgânica natural em sistemas aquáticos
Destin, comportement et écotoxicologie des nanoparticules d'argent: interactions avec les matières organiques naturelles dans les systèmes aquatiques
Keywords: nanoparticles; toxicity; humic substances; exopolysaccharides; silver